The ongoing antibiotic resistance and carbapenemase encoding genotypes surveillance. The first quarter report of the INVIFAR network for 2024. - Claudia Adriana Colín-Castro; Luis Esaú López-Jácome; María José Rodríguez-García; Melissa Garibaldi-Rojas; Fabián Rojas-Larios; María del Rosario Vázquez-Larios; Sandra Quintana-Ponce; Rafael Franco-Cendejas; Adolfo Gómez-Quiróz; Patricia Rodríguez-Zulueta; Thalia Rosado-Espinosa; Luis Javier Quintanilla-Cazares; et al. (PLoS ONE, 2025)
Introduction Antimicrobial resistance surveillance plays an important role in generating information about the prevalence of resistant microorganisms. In this study, we summarize a surveillance of antimicrobial resistance and carbapenemase-encoding genes for selected pathogens in Mexican healthcare centers. Methods Databases of identification and susceptibility results collected from January 1 to March 31, 2024, from forty-one centers were gathered and analyzed using the WHONET software. Some relevant gram-negatives and gram-positives, which were isolated from relevant clinical specimens were included. Isolates were stratified by patient´s age, clinical specimens, and site of attention, and were classified as multidrug-resistant (MDR). Clinical isolates were collected from January 1 to June 30 and were genotyped for carbapenemase-encoding genes by a polymerase chain reaction test. Results In total, 8 708 strains were included. Escherichia coli had a higher resistance to carbapenems (p < 0.05) in the 0–17 years group and Klebsiella pneumoniae (p = 0.017), Pseudomonas aeruginosa, and Acinetobacter baumannii (p < 0.05) in the 18–59 years group. P. aeruginosa had higher resistance to ceftazidime-avibactam, ceftolozane-tazobactam, cefepime, and imipenem (p < 0.05) in the 18–59 years group. K. pneumoniae had the highest resistance to carbapenems (p < 0.05) and cefepime (p < 0.001) in clinical isolates recovered from blood. For P. aeruginosa, the highest resistance to cefepime (p = 0.012) and ceftazidime (p < 0.018) was seen in isolates from urine. For Staphylococcus aureus, a higher resistance was observed for cefoxitin in lower respiratory tract specimens (p < 0.05). E. coli had the highest resistance to carbapenems (p < 0.01), and P. aeruginosa for ceftazidime (p = 0.005), cefepime (p = 0.003), piperacillin-tazobactam (p = <0.01), IPM (p = 0.006), and meropenem (p = <0.01) in clinical isolates recovered from patients in the intensive care unit (ICU). For K. pneumoniae, the highest resistance to ertapenem was observed in clinical isolates from the ICU area (p < 0.035). Finally, 67.9% of A. baumannii and 53.8% of E. coli strains were Multidrug-resistant. Candida albicans isolated from blood had susceptibility to caspofungin 100% and 90.2% for voriconazole. Regarding E. coli non-susceptible to meropenem, 16 (59.2%) were carriers of blaNDM, and the blaKPC gene was detected in 2 (40%) strains of K. pneumoniae. In conclusion, carbapenem resistance was higher for E. coli in the 0–17 years group and for K. pneumoniae, P. aeruginosa, and A. baumannii in the 18–59 years group. K. pneumoniae has the highest resistance to carbapenems in blood isolates and the ICU area. E. coli and P. aeruginosa had the highest carbapenem resistance in the intensive care unit. A high multidrug resistance was observed for A. baumannii and E. coli strains. A high susceptibility to caspofungin and voriconazole was observed for Candida albicans collected from blood.